Fiscal Federalism and Regional Performance - Di Bella, Gabriel (IMF Working Papers; Working Paper ;, 2017)
Sound regional policies are essential for balanced and sustained economic growth. The interaction of federal and regional policies with cross-regional structural differences affect human and physical capital formation, the business climate, private investment, market depth, and competition. This paper summarizes the main elements of Russia's fiscal federalism, describes the channels through which it operates, and assesses the effectiveness of regional transfers in reducing regional disparities. The results suggest that federal transfers to regions contributed to reducing disparities arising from heterogeneous regional tax bases and fiscal revenues. This allowed regions with initially lower per capita income to increase human and physical capital at higher rates. There is little evidence for transfers contributing to increased cross-regional growth synchronization. The results also suggest that federal transfers did not significantly improve regional fiscal sustainability, a conclusion that is supported by the lack of convergence in per capita real income across Russian regions in the last 15 years.